Denture labeling using QR codes : a simplified technique = Identificación de dentaduras completas utilizando códigos QR : una técnica simplificada - Jiménez Corrales, Rodrigo Antonio 1966-
Denture identification procedures have multiple benefits for denture wearers. These include prevention of losing or misplacing dentures and forensic identification of victims. A simplified inclusion technique is fully described to label dentures with QR code prints.